Intra‐operator and inter‐operator reliability of manual and semiautomated measurement of fetal nuchal translucency: a cross sectional study. (23rd October 2013) - Bakker, M.; Mulder, P.; Birnie, E.; Bilardo, C. M.
ABSTRACT Objective The goal of this study was to examine the intra‐operator and inter‐operator differences of the manual and semiautomated nuchal translucency (NT) measurements and to evaluate if these differences alter women's risk status. Methods A cross sectional study was performed. Two operators obtained manual and semiautomated NT measurements of 153 NT images. The maximal acceptable difference in NT measurements within and between operators was 0.15 mm. Intra and inter‐operator differences were analyzed by the paired Student's t‐test and homogeneity of variances by the Levene's test. Intra‐operator and inter‐operator agreement were quantified with Bland and Altman's limits of agreement, and changes in women's risk status were tested with the binomial test. Results Intra‐operator agreement was high for each of the measurement methods. Operator 1 had lower SDS for manual measurements. Conversely, operator 2 had lower SDS of the differences for semiautomated measurements, although the SD never reached the same level as operator 1. Inter‐operator agreement was highest for the semiautomated measurements. Changes in risk status occurred between the manual and inner‐middle method resulting in different clinical policies in up to 1 out of 20 cases. Conclusion Well‐trained operators do not seem to benefit from the use of the semiautomated measurement methods. © 2013 John Wiley & Sons, Ltd.